Эндодонтическое лечение в одно посещение: современные стандарты. Части VI-VII1 Лечение апикальных периодонтитов в одно посещение (часть 2) (Эндодонтия Today)
At the heart of contemporary approaches to endodontic treatment of teeth, of course, lies the teeth-saving technologies. The paper described the basic aspects of modern endodontics with references to world literature, introduces the concept of endodontic treatment of teeth in one visit, which the authors believe must now become the standard quality of endodontic treatment. The basis of the work is proposed by the author the protocol of apical periodontitis treatment in one visit.